Relationship between Resting Systemic Arterial Blood Pressure and Pain Sensitivity Parameters in Young Healthy Indian Medical Students - Mendpara, S J; Akhani, P N; Palan, B M; Harsoda, J M (Kathmandu University medical journal, 2019)
Background Pain interests clinicians and researchers alike. Several animal and human studies have attempted to establish and explain the relationship between blood pressure and nociception. Many studies have reported sex differences in pain perception in humans. However, there is no consistent evidence that authoritatively explains the relationship between resting systemic arterial blood pressure and pain sensitivity parameters in human subjects. Objective To investigate the relationship between resting systemic arterial blood pressure and pain sensitivity parameters. Secondary objectives were to investigate blood pressure response to cold pain and sex differences in response to cold pain and pain perception. Method Out of a total of 331 volunteers, 200 students (100 males and 100 females) were selected for study as per the inclusion and exclusion criteria. Cold Pressor Test was used to apply experimental pain. To study response, cardiovascular parameters (systolic blood pressure and diastolic blood pressure) and pain sensitivity parameters (pain threshold, pain tolerance and pain rating) were measured. Result Rise in resting systolic and diastolic blood pressure following Cold Pressor Test was similar between both the sexes (p > 0.05). Pain rating was found to be significantly higher in females whereas pain threshold and pain tolerance were significantly higher in males (p < 0.05). Resting blood pressure showed a positive relationship with pain threshold and pain tolerance whereas a negative relationship with pain rating. Conclusion Resting systemic arterial blood pressure and pain sensitivity are inversely correlated. Females are more sensitive to pain than males.